The Impact of Service Quality and Sharia Governance on Cooperative Members’ Loyalty of Post Conversion as Mediated by Brand Image - Ridwan Nurdin; Muhammad Haris Riyaldi; Sakinatul Raadiyah Abdullah; Khairil Umuri (Yayasan Darussalam Bengkulu, 2026)
Background: The growth of sharia cooperatives in Aceh following the implementation of Qanun No. 11/2018 Aceh has intensified competition and highlighted the importance of maintaining member loyalty. Factors such as service quality, sharia governance, and institutional image are crucial in influencing satisfaction and sustaining cooperative member loyalty. Method: This study utilized primary data by distributing questionnaires to 113 respondents through cluster sampling, namely sharia cooperatives located in the West, East, and Central Aceh regions. We tested the seven proposed hypotheses using the Structural Equation Modeling (SEM) technique. Results: The findings of this study indicate that service quality and sharia governance have an effect on the institution's ideals. Likewise, service quality has an effect on member loyalty. However, sharia governance and brand image do not have an effect on member loyalty. The indirect effect also reveals that the brand image cannot influence service quality or sharia governance's effect on member loyalty. The study investigates the mediated effect of sharia governance and service quality on member loyalty. Conclusion: This empirical evidence demonstrates that sharia cooperatives need to improve the quality of their services in order to preserve member loyalty